Primary and secondary processes in the nanosecond range in the production of a discharge in a short gas gap; Journal of Applied Mechanics and Technical Physics; Vol. 9, № 3 - Mesyats G. A. Gennady Andreyevich; Iskol'dskii A. M.; Kremnev V. V.; Bychkova L. G.; Bychkov Yu. I. (1968, 1968)
В фонде НТБ ТПУ отсутствует